Tourism Marketing Strategies and Destination Branding in Southern West Bengal: A Comparative Analysis of Kolkata, South 24 Parganas, Bankura and Purulia. (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Tourism marketing in emerging regional destinations demands more than generic promotional effort it requires an understanding of the unique competitive landscape, cultural assets, and infrastructure realities of each locale. This paper examines tourism marketing strategies and destination branding across four southern districts of West Bengal, India: Kolkata, South 24 Parganas, Bankura, and Purulia. Drawing on a comprehensive review of secondary data, district-level SWOT analyses, and an empirical tourist survey (n = 600), the study assesses how current marketing strategies perform across the extended 7Ps marketing mix and identifies critical gaps in branding, digital communication, and institutional coordination. Findings reveal that while Kolkata operates as a mature, multi-channel tourism destination, the remaining three districts despite possessing internationally significant cultural and natural assets suffer from weak digital presence, fragmented promotion, and inadequate destination branding. The study proposes a differentiated, district-specific branding framework grounded in each destination's Unique Selling Proposition (USP), and recommends strategic investments in digital transformation, community-based marketing, and cross-district tourism circuits. The research contributes empirically to destination marketing literature in the context of an emerging Indian tourism region and offers practical guidance for tourism planners, destination management organizations (DMOs), and policy-makers.